Implementasi Social Media Marketing pada Social Media Facebook dalam Upaya Meningkatkan Penjualan Bisnis Jasa Wedding Organizer - Hasna Safa Safira; Erna Maulina; Cecep Safa’atul Barkah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to implement a social media marketing plan as a strategic effort to increase sales at Mee Gallery Wedding Sukabumi. The research adopts a descriptive qualitative approach with data collected through interviews, observations, and documentation. The project was carried out over a period of three months and refers to Barker's eight stages of social media marketing strategy, namely: listening, goal setting, defining strategy, identifying the target market, selecting tools, selecting platforms and channels, implementation, and monitoring. The implementation results show a 100% increase in the number of followers, a 26,600% growth in audience engagement, and a significant rise in the number of messages from potential customers via WhatsApp. The average monthly sales also increased to 2 to 5 clients, resulting in a total sales growth of 35.32% compared to the previous period. In addition to its impact on sales, the strategy contributed to strengthening brand identity, enhancing audience engagement, and improving the internal workflow of the digital marketing team. In conclusion, a well-structured and consistently executed social media marketing strategy has proven to be a relevant and effective solution in supporting the success of Mee Gallery Wedding Sukabumi in increasing sales in the digital era.